Leopold Anton Kaufhold: visión antitética de España - Esteve Montenegro, María Luisa (Revista de Filología Románica, 2006)
In this paper the authoress presents some aspects of the objective and impartial view, –though not always free from contradictions– which the first German traveller on Spanish lands, Leopold A. Kaufhold had at the end of the XVIII century. His description fluctuates from the Enlightenment to the Romantic Movement, without being able to integrate both perspectives in complete harmony, but he manages to transmit interesting considerations with regard to the inhabitants, their scenery, the importance of mining and the need of specialized labour at that time.